2021
DOI: 10.1073/pnas.2025102118
|View full text |Cite
|
Sign up to set email alerts
|

A RIPK1-regulated inflammatory microglial state in amyotrophic lateral sclerosis

Abstract: Microglial-derived inflammation has been linked to a broad range of neurodegenerative and neuropsychiatric conditions, including amyotrophic lateral sclerosis (ALS). Using single-cell RNA sequencing, a class of Disease-Associated Microglia (DAMs) have been characterized in neurodegeneration. However, the DAM phenotype alone is insufficient to explain the functional complexity of microglia, particularly with regard to regulating inflammation that is a hallmark of many neurodegenerative diseases. Here, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 59 publications
1
39
1
Order By: Relevance
“…Even though there is no causal evidence linking RIPK1 mutations to ALS, this gene was shown to mediate axonal degeneration by promoting inflammation and subsequent oligodendrocytes necroptosis in ALS [33], and a proinflammatory role of RIPK1 kinase activity in the CNS in association with TBK1 was demonstrated, as mentioned above [27]. Importantly, a recent study based on single-cell RNA sequencing has identified a RIPK1-regulated inflammatory microglial (RRIM) subset in early-stage SOD1 G93A mice [34]. Differently from Disease-Associated Microglia (DAM), the RRIM state was characterized by up-regulation of classic proinflammatory pathways, and was found to peak at an earlier time point in the ALS model, compared to the DAM phenotype [34].…”
Section: Ripk1 (Receptor-interacting Kinase 1)mentioning
confidence: 99%
“…Even though there is no causal evidence linking RIPK1 mutations to ALS, this gene was shown to mediate axonal degeneration by promoting inflammation and subsequent oligodendrocytes necroptosis in ALS [33], and a proinflammatory role of RIPK1 kinase activity in the CNS in association with TBK1 was demonstrated, as mentioned above [27]. Importantly, a recent study based on single-cell RNA sequencing has identified a RIPK1-regulated inflammatory microglial (RRIM) subset in early-stage SOD1 G93A mice [34]. Differently from Disease-Associated Microglia (DAM), the RRIM state was characterized by up-regulation of classic proinflammatory pathways, and was found to peak at an earlier time point in the ALS model, compared to the DAM phenotype [34].…”
Section: Ripk1 (Receptor-interacting Kinase 1)mentioning
confidence: 99%
“…Models of other lower motor neuron (LMN) degeneration including Sod1 and Optn deficient mouse models of ALS demonstrate the interplay between microglia and oligodendrocytes influencing LMN cell survival at the spinal cord level [ 103 ]. Microglial proliferation, cytokine release, and activation of receptors such as RIPK1 are a critical component of cell death in neurodegeneration [ 103 105 ].…”
Section: Symptom Progression In Late-onset Gm2 Gangliosidosesmentioning
confidence: 99%
“…Models of other lower motor neuron (LMN) degeneration including Sod1 and Optn deficient mouse models of ALS demonstrate the interplay between microglia and oligodendrocytes influencing LMN cell survival at the spinal cord level [ 103 ]. Microglial proliferation, cytokine release, and activation of receptors such as RIPK1 are a critical component of cell death in neurodegeneration [ 103 105 ]. “Cross-talk” between activated microglia and oligodendrocytes results in subclasses of microglia that are directly involved in neurodegeneration, loss of myelin coverings and subsequent retrograde degeneration of anterior horn cells [ 104 ].…”
Section: Symptom Progression In Late-onset Gm2 Gangliosidosesmentioning
confidence: 99%
“…Another is cleavage of RIPK1 by caspase-8. Both mechanisms could serve as potential regulatory mechanisms to promote survival of microglia and macrophages, or to direct inflammatory signaling away from a neurodegenerative RIPK1-dependent pro-inflammatory phenotype such as that observed in a subclass of microglia in ALS models [ 68 ]. These speculations deserve further investigation in CCI models.…”
Section: Discussionmentioning
confidence: 99%